Channel equalization for block transmission systems - Kaleh, G.K. (IEEE journal on selected areas in communications, 1995)
In a block transmission system the information symbols are arranged in the form of blocks separated by known symbols. Such a system is suitable for communication over time-dispersive channels subject to fast time-variations, e,g., the HF channel. The known reliable receiver for this system is the nonlinear data-directed estimator (NDDE). This paper presents appropriate equalization methods for this system. A nonstationary innovations representation based on Cholesky factorization is used in order to define a noise whitener and a maximum-likelihood block detector. Also block linear equalizers and block decision-feedback equalizers are derived. For each type we give the zero-forcing and the minimum-mean-squared-error versions. Performance evaluations and comparisons are given. We show that they perform better than conventional equalizers. As compared to the NDDE, the derived block decision-feedback equalizers perform better and are much less complex. Whereas the NDDE uses the Levinson algorithm to solve M/2 Toeplitz systems of decreasing order (where M is the number of symbols per block), the derived equalizers need to process only one Toeplitz system. Moreover, the Schur algorithm, proposed for Cholesky factorization allows us to further reduce the complexity.< >